Increasing Rates of Pediatric Empyema and Disease Severity With Predominance of Serotype 3 S. pneumonia: An Australian Single-center, Retrospective Cohort 2011 to 2018. Issue 12 (December 2019) - Haggie, Stuart; Fitzgerald, Dominic A.; Pandit, Chetan; Selvadurai, Hiran; Robinson, Paul; Gunasekera, Hasantha; Britton, Philip
Abstract : Background: The impact of universal 13-valent pneumococcal conjugate vaccine immunization on pediatric empyema rates and pathogens in Australia is not known. We aimed to describe empyema epidemiology, clinical characteristics and treatment during an 8-year period. Methods: A retrospective study between 2011 and 2018 of empyema cases admitted to a large pediatric referral hospital, for management with either pleural drainage and fibrinolytics or surgical intervention. Results: There were 195 cases in 8 years. Empyema incidence and ICU admission rates significantly increased during the study with a peak incidence of 7.1/1000 medical admissions in 2016 (χ 2 for trend of incidence 37.8, P < 0.001 and for ICU admissions 15.3, P < 0.001). S. pneumoniae was the most common pathogen (75/195, 39%) with serotype 3 the most detected (27/75: 27%). S. pyogenes compared with S. pneumoniae had significantly fewer days of fever before admission (3.9 vs. 6.4, mean difference 2.4, 95% CI: 0.84–4.08, P = 0.003) and higher proportion requiring direct ICU admission (6/75; 8% vs. 7/15; 47%, P < 0.001). Compared with S. pneumoniae, cases with no pathogen detected by culture or PCR had fewer days of fever post intervention (4.4 vs. 7.4 days, mean difference 2.7 days, P = 0.002). S. aureus occurred more commonly in infants (10/25; 40% vs. 1/75; 1%, P < 0.001) and children of indigenous background (5/25; 20% vs. 1/75; 1%, P < 0.001) compared with S. pneumoniae . Conclusions: We report increasing rates of pediatric empyema with higher proportions requiring ICU treatment. The most common pathogens detected were S. pneumoniae, S. aureus and S. pyogenes . Despite high 13-valent pneumococcal conjugate vaccine coverage, serotype 3 was the most common S. pneumoniae serotype identified.